Dengue Fever Presenting with Concomitant Acute Coronary Syndrome (ACS) - A Series of 5 Cases At A Tertiary Care Hospital In Dhaka (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Dengue fever may present with many cardiovascular manifestations contributing to death and disability. Acute Coronary Syndrome (ACS) during dengue is rare but poses important management dilemma. Here we present a series of 5 patients with dengue fever who developed different types of ACS during the ongoing dengue endemic in Bangladesh.Five patients admitted with dengue fever and who developed ACS between 1st July to 30th September 2023 at Medicine Department of Uttara Adhunik Medical College, Dhaka, Bangladesh were studied. All the patients had some co[1]morbidity like diabetes, hypertension, or both. Treatment of ACS was tailored according to their CBC report, most importantly, platelet count, and hematocrit.Four out of the 5 patients responded well to anti-ischemic therapy, even though anti-platelet and anti-coagulants could not be given in all cases.There was 1 fatality, but that was due to ARDS consequent due to severe bilateral pneumonia. Management of ACS in dengue is challenging. Physicians should have appropriate preparedness to deal with these cases.J Bangladesh Coll Phys Surg 2023; 41: 82-87